PENGARUH PENGGUNAAN METODE PEMBELAJARAN GIVING QUESTION AND GETTING ANSWER TERHADAP MOTIVASI BELAJAR PPKn SISWA KELAS VII MTs NEGERI 1 INDRAGIRI HULU - Apriandi Arifwan; Gimin Gimin; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of using Giving Question and Getting Answer learning method toward social students motivation in learning PPKn at MTs Negeri 1 Indragiri Hulu. This study aims to determine the effect of of using Giving Question and Getting Answer learning method toward students’ motivation in learning PPKn at MTs Negeri 1 Indragiri Hulu.This research was a quantitative descriptive study that was experimental. Population in this study were social students of class VII MTs Negeri 1 Indragiri Hulu. The sample in this research was taken based on "Multi Stage Random Sampling" technique. Where the class taken into the sample was the students of class VII 2 (experimental class) who were given the Giving Question and Getting Answer learning method, and class VII 3 (control class).Taken randomly were students who were given the conventional method. Then data analysis by using homogeneity test and "t" test. Based on the result of research indicated that there wasan effect of learning motivation between student who using Giving Question and Getting Answer learning method and conventional method in MTs Negeri 1 Indragiri Hulu (>).Where there was an average increase toward motivation in learning PPKn of experimental class  from 20,12  to 22,93 and the average of PPKn learning motivation of control class from 16,75 to 18,81. Thus the hypothesis which reads that there is an effect of using Giving Question and Getting Answer learning method toward learning motivation of PPKn student at MTs Negeri 1 Indragiri Hulu, can be accepted. Key Words : Effect, Giving Question and Getting Answer, Motivation